Mobile Phone Messaging During Unobserved "Home" Induction to Buprenorphine. Issue 5 (September 2016) - Tofighi, Babak; Grossman, Ellie; Sherman, Scott; Nunes, Edward V.; Lee, Joshua D.
Abstract : The deployment of health information technologies promises to optimize clinical outcomes for populations with substance use disorders. Electronic health records, web-based counseling interventions, and mobile phone applications enhance the delivery of evidence-based behavioral and pharmacological treatments, with minimal burden to clinical personnel, infrastructure, and work flows. This clinical case shares a recent experience utilizing mobile phone text messaging between an office-based buprenorphine provider in a safety net ambulatory clinic and a patient seeking buprenorphine treatment for opioid use disorder. The case highlights the use of text message-based physician–patient communication to facilitate unobserved "home" induction onto buprenorphine.